Implementasi Konsep 4A dan Carrying Capacity dalam Pengembangan Pulau Reusam Menjadi Kawasan Ekowisata Berbasis Syariah - Izwar Izwar; Dian Kristanti (Journal on Education, 2023)
The increase in tourists visiting Reusam Island increases the risk of environmental damage, neglecting this problem will have an impact on other social problems, resulting in the death of tourism activities. Efforts to overcome the above problems by accommodating various interests and adjusting to the implementation of Islamic Sharia in Aceh Jaya. This research applies a sequential explanatory method. Sundays up to 500 people. While the FGD data analysis regarding the suitability of implementing the 4A concept (Attraction, Accessibility, Amenities, Ancillary Services) on Reusam Island, it still needs to be adjusted in its application in the field, because there are differences in management systems between conventional tourism management and sharia ecotourism